(untitled) (Vietnam Journal of Community Medicine, 2025)
Objectives: Description of Patulin contamination in fruit juices and fruit products, samples collected at traditional markets in Can Tho city, December 2024. Methods: A total of 160 fruit juices and fruit products were analyzed for Patulin quantification. Mycotoxin analysis was performed by high-performance liquid chromatography with a UV detector. Test results are evaluated according to QCVN No. 8-1:2011/BYT. Results: The average concentration of Patulin in fruit juices and fruit products was 24.9 µg/kg; spirit drinks, cider, fermented apple drinks was 22.72 µg/kg; apple products (fruit pulp), apple jam used as food was 9.02 µg/kg; and apple juice, apple products for children under 36 months of age was 5.13 µg/kg. The results showed that 56.25% of the samples were contaminated with mycotoxins and 14.4% of the samples exceeded the allowable standard. Conclution: 14.4% of fruit juice and fruit product samples taken at traditional markets in Can Tho city in 2024 had Patulin concentrations exceeding the permissible limit.